DJ-1 inhibits glutathione degradation by downregulating CHAC1 expression in astrocytes. (November 2022) - Ge, Yuan; Zheng, Xinlei; Mao, Shiyu; Zhang, Qingyu; Hu, Gang; Wei, Yao
Abstract: The PARK7 gene, which encodes DJ-1 protein, is the causative gene of autosomal recessive early-onset Parkinson's disease. DJ-1 has many biological functions, including regulating glutathione (GSH) levels. However, the molecular mechanism by which DJ-1 regulates GSH levels in astrocytes remains unclear. With high throughput sequencing, we discovered that DJ-1 knockout could significantly upregulate the expression of ChaC glutathione-specific gamma-glutamylcyclotransferase 1 (CHAC1). We demonstrate that DJ-1 can bind with the basic leucine zipper domain of activating transcription factor 3 (ATF3) through bimolecular fluorescence complementation. Besides, DJ-1 inhibits ATF3 binding to the CHAC1 promoter and downregulates the expression of CHAC1 to reduce GSH degradation. Our research suggests that the loss of DJ-1 in astrocytes promotes the degradation of GSH, leading neurons more vulnerable to oxidative damage. It provides a theoretical basis for developing drugs targeting DJ-1 and GSH in the brain. Highlights: DJ-1 in astrocytes can regulate glutathione levels. CHAC1 expression is elevated in DJ-1 knockout cells. DJ-1 binds to the basic leucine zipper domain of ATF3 to inhibit its binding to the CHAC1 promoter. DJ-1 inhibits glutathione degradation by downregulating CHAC1 expression.